Paradigma Wakaf Produktif dalam Al-Qur’an: Dari Konsep Normatif Menuju Praktik Kontemporer - Ridhoul Wahidi (SETYAKI : Jurnal Studi Keagamaan Islam, 2026)
Productive waqf (wakaf produktif) has become one of the most strategic instruments of Islamic social finance for community economic empowerment, yet its normative foundation in the Qur'an is often understood only partially, separated from its contemporary institutional practice. This study aims to trace the paradigm of productive waqf from its normative basis in the Qur'an to its transformation into contemporary legal and institutional practice in Indonesia. This research uses a qualitative approach with a library research (normative-doctrinal) method, analyzing Qur'anic verses related to infaq and sadaqah jariyah (QS. Ali 'Imran: 92; QS. Al-Baqarah: 261-267; QS. Al-Hajj: 77), classical and contemporary tafsir, fiqh literature, statutory regulations, and recent scholarly studies. The results show that although the term waqf is not explicitly mentioned in the Qur'an, its normative basis is derived through ijtihad from verses commanding the spending of one's most beloved wealth (al-birr) and continuous charity (sadaqah jariyah). This normative concept has evolved through classical fiqh codification, national legal institutionalization under Law No. 41 of 2004 on Waqf, and finally into contemporary productive practices such as commercial waqf assets, waqf shares, cash waqf, and Cash Waqf Linked Sukuk (CWLS). The study finds that the success of productive waqf depends on the professionalism of nazhir (waqf administrators), regulatory support, digitalization, and public literacy. This study contributes a conceptual bridge connecting Qur'anic normative theology with the empirical development of Islamic social finance institutions in contemporary Indonesia.